1974
DOI: 10.1088/0029-5515/14/1/013
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic systems of the stellarator type in the presence of a solenoid with a helical magnetic axis

Abstract: An investigation is made of a magnetic configuration formed by a combination of fields from a solenoid with a helical magnetic axis and a plane-geometry axis and stellarator helical conductors. The paper contains analytical expressions for the determination of the characteristics of the magnetic configuration, examples of magnetic surfaces of the system in a rectilinear approximation and the results of a numerical calculation of a toroidal variant of the configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Two typical winding laws were considered which correspond to the following values of the coefficient a: oc = -1 and a = 1. At a = -1, relatively low magnetic surface distortions [6,7] produce a substantial theoretical confinement volume. Such a winding law is close to the optimum obtained in Ref.…”
Section: Configuration Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Two typical winding laws were considered which correspond to the following values of the coefficient a: oc = -1 and a = 1. At a = -1, relatively low magnetic surface distortions [6,7] produce a substantial theoretical confinement volume. Such a winding law is close to the optimum obtained in Ref.…”
Section: Configuration Parametersmentioning
confidence: 99%
“…Some common features of the L-H transition are the existence of a threshold heating power and a sharp drop of the edge magnetic and density fluctuations and of the H a /D a signals after the transition. On the basis of previous theoretical studies, Ohyabu et al [7] suggested that the L-H transition corresponds to a stabilization of microtearing modes with poloidal mode number m 5: 8 when the edge temperature exceeds a certain threshold. His stabilization criterion is probably oversimplified, since the edge plasma profiles change rapidly in the radial direction; furthermore, the parameter ranges in previous studies of microtearing modes are not applicable to the edge of tokamaks such as DIII-D.…”
mentioning
confidence: 99%